The Uses of First Person Writings / Les usages des écrits du for privé - Roland, Hubert,Ruggiu, François-Joseph (P.I.E-Peter Lang S.A., 2013)
This book considers first-person writing and the related questions of the formation of the self, the rise of the individual and the private/public debate, and places these considerations within a multicultural perspective. It compares the characteristics of European or Occidental personal writings (such as diaries, memoirs and autobiographies) with the written forms of personal, intimate and autobiographical self which have existed and continue to exist within various Asian, African or Near Eastern cultures. The book constitutes a call for a global history of personal writing. Ce livre s’intéresse, dans une perspective multiculturelle, à l’écriture de soi, et aux questions connexes de la formation même du soi, de l’émergence de l’individu ou encore du débat sur l’apparition des sphères privées et publiques. Il compare les caractéristiques de l’écrit personnel tel qu’il a eu cours en Europe ou dans les pays occidentaux (comme les journaux intimes, les mémoires, les autobiographies, entre autres) avec les formes écrites du soi personnel, intime ou autobiographique telles qu’elles ont pu exister, et existent, dans différentes cultures asiatiques, africaines ou proches-orientales. Ce livre lance également un appel pour une histoire globale des écrits personnels. «Dieser Sammelband vereinigt Aufsätze auf insgesamt hohem Niveau, die methodische Überlegungen mit einem beeindruckend weiten und gut präsentierten Spektrum an Quellen verbinden. Der Band bietet einen hervorragenden Einstieg in die ‘first person writings’ mit vielen weiterführenden Fragen zur Frage, was ‘ich’ jeweils heissen kann.» (Almut Höfert, L’Homme 24, 2013/2)...
10.3726/978-3-0352-6309-1
Keywords: Aufsatzsammlung; Autobiografie; Ich-Erzählung